The dependence of long-wave radiation on cloudiness, water vapour content and temperature - KELKAR , R. R.; GODBOLE, R. V. (MAUSAM, 1970)
Long wave radiative heat fluxes and cooling rates have been computed for a model atmosphere representing mean conditions over the Indian region during the monsoon season. Variations values of flux and cooling rate for given deviations from the model atmosphere have been studied, the individual contributions of cloudiness, water vapour content and temperature to the radiative processes have been assessed separately. It is found that a change in the cloud amount causes large changes in the cooling rate near the top and base of the cloud, but does not significantly alter the integrated cooling of the atmospheric column. The integrated however, increases with a decrease in the height of the top or base. The upward flux at any level strongly controlled by the surface temperature, wherea6 the downward dux is largely dependent on the water vapour content above the level.